2012
DOI: 10.1038/onc.2011.640
|View full text |Cite
|
Sign up to set email alerts
|

Genetic insight and therapeutic targets in squamous-cell lung cancer

Abstract: Squamous-cell lung cancer is one of the most prevalent subtypes of lung cancer worldwide and its pathogenesis is closely linked with tobacco exposure. Unfortunately, squamous-cell lung cancer patients do not benefit from major advances in the development of targeted therapeutics such as epidermal growth factor receptor (EGFR) inhibitors or anaplastic lymphoma kinase (ALK) inhibitors that show exquisite activity in lung adenocarcinomas with EGFR mutations or echinoderm microtubule associated protein like-4 (EML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…In summary, our analysis showed that a shorter smoking history and central localization of SCC tumors were related to a better survival outcome (Clus 1); while a long smoking history and peripheral distribution of tumors appeared to associate with a poor survival (Clus 2). Furthermore, our findings about the associations between survival outcomes and clinical factors in SCC patients are consistent with previous reports [24][25][26][27]. Moreover, statistical analysis on tobacco consuming history and initial age of diagnosis indicated that the old people with a long smoking history are more vulnerable.…”
Section: Clinical Characteristics Of Scc Subgroupssupporting
confidence: 81%
See 2 more Smart Citations
“…In summary, our analysis showed that a shorter smoking history and central localization of SCC tumors were related to a better survival outcome (Clus 1); while a long smoking history and peripheral distribution of tumors appeared to associate with a poor survival (Clus 2). Furthermore, our findings about the associations between survival outcomes and clinical factors in SCC patients are consistent with previous reports [24][25][26][27]. Moreover, statistical analysis on tobacco consuming history and initial age of diagnosis indicated that the old people with a long smoking history are more vulnerable.…”
Section: Clinical Characteristics Of Scc Subgroupssupporting
confidence: 81%
“…There were 10 genes with a false discovery rate (FDR) Q value less than 0.1, including TP53, CDKN2A, PTEN, PIK3CA, KEAP1, MLL2, HLA-A, NFE2L2, NOTCH1, and RB1. The mutation rates of genes characterized previously in SCC (AKT1, DDR2, EGFR, BRAF, MET) [24] were also listed in the Figure 5A. Most of genes had missense mutation, which may result in changes in a coding sequence.…”
Section: Genomic Characteristics For Dlsa Subtypes Of Scc Somatic Genmentioning
confidence: 99%
See 1 more Smart Citation
“…In lung adenocarcinoma, KRAS mutations are more common in smokers (12)(13)(14)(15)(16). The prognostic significance of KRAS mutations in NSCLC is controversial (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…There is a dire need to further clarify and identify additional driver oncogenes in squamous cell carcinoma and other subtypes (including small cell lung cancers and other rare neoplasms of the lung) in order to identify amenable therapeutic targets for these patients. 81 EPIGENETIC CHANGES Gene promoter methylation, histone modification, and regulation by microRNAs are the 3 common epigenetic phenomena, that indirectly influence the process of carcinogenesis by modulating gene mutation and expression. Aberrant DNA methylation is a well-studied mechanism for the inactivation of tumor suppressor genes.…”
Section: Therapeutic Targets In Squamous Cell Carcinomamentioning
confidence: 99%